University student strategies to cope with anxiety in learning English - Joppi Rondonuwu (Universitas Ahmad Dahlan)
This article has been prepared to report a quantitative study that revealed the strategies of students of English major and non-English major to cope with anxiety in the learning of English as a foreign language, including the description of student anxiety in learning English and strategies to cope with English learning. The respondents consisted of 173 students from English major and 173 students from non-English major of a private university in North Sulawesi Province. The validated adapted constructs of the questionnaire, namely strategies and anxiety, were originally proposed by He and Horwitz, Horwitz, and Cope respectively. The research findings showed that both English major and non-English major students had no significant difference in their strategies to cope with anxiety in learning English and in their level of anxiety in learning English. However, there were four strategies to cope with anxiety in learning English which significantly contributed to the anxiety in learning English as a foreign language.